Perbedaan Kemandirian Activity Of Daily Living Antara Penderita Low Back Pain Intensitas Nyeri Ringan Dengan Penderita Low Back Pain Intensitas Nyeri Sedang Di Desa Sobokerto Kecamatan Ngemplak Kabupaten Boyolali - Wawan Ridwan Mutaqin; Rina Kurnia (Jurnal Keterapian Fisik, 2016)
Abstract: Low Back Pain, Pain Intensity, ADL Independency Level. The research aimed to reveal the dissimilarity of ADL independency on people with lower back pain (LBP) which varied from mild to moderate pain intensity. LBP means continuous pain which persists on the back side of the body span from lower ribs bone to coccyx bone and expand from upper back to the crotch. The research was comparing the level of independency in people with varied LBP intensity. The research conducted in Sobokerto, Ngemplak, Boyolali involving 50 respondents consisted of 25 respondents with mild pain intensity and 25 respondents with moderate pain intensity. Numeric Rating Scale (NRS) used as the research instrument to measure pain intensity and Barthel Index used as the tool to measure ADL independency level. The research designed is cross sectional and Mann Whitney U were used as the analytical method. The data were analyzed with the use of SPSS 16 for windows. P value obtained as 0.000 (< 0.05) troughs the analytical test of Mann Whitney U. The research depicts clear evidence of different level on performing ADL independency in people with LBP within mild and moderate pain intensity.